Encyclopedia of Computational Mechanics 2004
DOI: 10.1002/0470091355.ecm036
|View full text |Cite
|
Sign up to set email alerts
|

Computational Modelling of Damage and Failures in Composite Laminates

Abstract: This chapter provides an overview of issues that are important in finite element modeling of progressive damage and failure in fiber‐reinforced composite laminates. Topics discussed include the multiscale nature of composite laminate problems, equivalent single layer and layerwise laminate theories and models, macroscopic failure theories, computational homogenization and localization, and the application of continuum damage mechanics to composite laminate problems, with emphasis on methods that are practical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…For several decades, thin laminated structures of this type have been the focus of intensive research, aimed at the development of theoretical and computational formulations capable of predicting their performance characteristics and service life, both accurately and efficiently. Contributions to this field of research are surveyed and catalogued in several review articles [1][2][3][4] found in the literature; see also Ref. [5] for a more detailed exposition.…”
Section: Introductionmentioning
confidence: 99%
“…For several decades, thin laminated structures of this type have been the focus of intensive research, aimed at the development of theoretical and computational formulations capable of predicting their performance characteristics and service life, both accurately and efficiently. Contributions to this field of research are surveyed and catalogued in several review articles [1][2][3][4] found in the literature; see also Ref. [5] for a more detailed exposition.…”
Section: Introductionmentioning
confidence: 99%